ANALISIS POSITIONING PURA ULUWATU SEBAGAI DAYA TARIK WISATA DI BALI - Liestiandre, Hanugrah Kristiono (JURNAL KEPARIWISATAAN, 2017)
The existence of Pura in Bali is not only as a place of worship for Hindus, but int he development of tourism in Bali, Pura has become a tourist attraction attracted by tourists to visit. Besides the cultural and religious values that tourists can get, the historical value and the architectural beauty and the natural location and the confusion that becomes part of the temple in Bali are included in the list of tourist arrivals visiting Bali. Characteristics of each temple can be used as uniqueness and competitive advantage, and help tourists when they want to choose a temple in Bali. Analytical techniques used in this study are Multi Dimensional Scaling (MDS) and Correspondence Analysis (CA) to determine the advantages of each attribute for each tourist attraction. The results of this study show the positioning of Uluwatu Temple as a tourist attraction in Bali has similarities with Pura Tanah Lot. Based on the assessment of the ten attributes assessed by the respondents, it appears that overall Pura Uluwatu has a positive perception that varies compared to other temples. Pura Uluwatu has an advantage on uniqueness and scenery attributes.